Casual Academic Staff in an Australian University: Marginalised and Excluded - Ryan, S.; Burgess, John; Connell, Julia; Egbert, G. (Routledge, 2013)
Over the past 25 years, the Australian workforce has become more casualised, with approximately one-quarter of the workforce in casual employment today. One of the highest users of casual employees is the higher education sector, where casual academics (referred to as sessionals in the Australian context) are estimated to account for 50% of the overall teaching load. The purpose of this article is to investigate the processes associated with the management of sessional academic staff. The study focuses on a single university, utilising a survey questionnaire and interviews with the sessional academics and their managers. The results depict a bifurcated system of maximum labour regulation for full-time academics alongside minimum regulation for sessional staff. The findings stress the urgency for improvement in both the employment conditions and management of sessional academic staff, both for their own benefit and the universities that employ them.